DINAMIKA BUDAYA BANDA: Kajian Historis dan Antropologis atas Warisan Budaya Terbuka - Latora, Rusdan (BANDA HISTORIA: Jurnal Pendidikan Sejarah dan Studi Budaya, 2025)
This study aims to trace the historical roots of cultural openness in the Banda community, describe its concrete manifestations in social life, customs, architecture, and culinary practices, and analyze its continuity in the era of globalization. The research employs a descriptive qualitative approach with ethnographic-historical methods, involving literature review, participatory observation, and in-depth interviews with traditional leaders and community members. The findings reveal that the cultural openness of the Banda people was shaped through trade networks, intermarriage, religious missions, and colonialism, resulting in an inclusive cultural heritage. This openness is reflected in social tolerance, the integration of religious values into customary practices, the fusion of local and colonial architecture, and cuisine influenced by various nations. Amid the currents of globalization, despite facing the challenges of cultural homogenization, the Banda community continues to uphold the values of openness through social practices, traditions, and local cultural preservation. This study affirms that Banda’s cultural openness is not a passive attitude toward external influences, but rather a selective and reflective process that constitutes an essential identity for Indonesia’s multicultural society.